Exploring Micro-Eukaryotic Diversity in the Gut: Co-occurrence of Blastocystis Subtypes and Other Protists in Zoo Animals - Betts, Emma L.; Gentekaki, Eleni; Tsaousis, Anastasios D. (Frontiers in Microbiology, 2020)
Blastocystis is a genetically diverse microbial eukaryote thriving in the gut of humans and other animals. While Blastocystis has been linked with gastrointestinal disorders, its pathogenicity remains controversial. Previous reports have suggested that one out of six humans could be carrying Blastocystis in their gut, while the numbers could be even higher in animals. Most studies on Blastocystis are either exclusively targeting the organism itself and/or the associated prokaryotic microbiome, while co-occurrence of other microbial eukaryotes has been mainly ignored. Herein, we aimed to explore presence and genetic diversity of Blastocystis along with the commonly occurring eukaryotes Cryptosporidium, Eimeria, Entamoeba and Giardia in the gut of asymptomatic animals from two conservation parks in the UK. Building upon a previous study, a total of 231 fecal samples were collected from 38 vertebrates, which included 12 carnivorous and 26 non-carnivorous species. None of the animals examined herein showed gastrointestinal symptoms. The barcoding region of the small subunit ribosomal RNA was used for subtyping of Blastocystis. Overall, 47% of animal species were positive for Blastocystis. Twenty six percent of samples carried more than one subtypes, including the newly identified hosts Scottish wildcat, bongo and lynx. Fifty three percent of samples carried at least another microbial eukaryote. Herewith, we discuss potential implications of these findings and the increasingly blurred definition of microbial parasites.